Hermeneutika Agama Islam: Menempatkan Relevansi Agama dan Kesalehan Sosial - Kusmana Kusmana (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
Hermeneutics, or the understanding and interpretation of the role of religion in the context of individual or societal life, positions religion as one of the guiding principles alongside others. In this position, the role of religion is subject to controversy, with at least two major groups: those who consider it important and those who see it as an obstacle to human life. Figures such as Nimrod, Pharaoh, Sigmund Freud, Karl Marx, Nietzsche, and others, in their respective emphases, view the socio-political role of religion as hindering societal progress, threatening the power and systems established by religious, cultural, or political elites. Conversely, another significant group does not doubt the role of religion in human life at all. Religion serves as guidance for humans towards salvation and happiness in both the worldly life and the hereafter. This article seeks to examine the important role of religion (specifically Islam) in all aspects of human life as an actualization of Islam's mission as a mercy to the entire universe, with a strong social dimension.